2017
DOI: 10.1371/journal.pone.0173400
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma cells undergo aggressive coalescence in a 3D Matrigel model that is repressed by anti-CD44

Abstract: Using unique computer-assisted 3D reconstruction software, it was previously demonstrated that tumorigenic cell lines derived from breast tumors, when seeded in a 3D Matrigel model, grew as clonal aggregates which, after approximately 100 hours, underwent coalescence mediated by specialized cells, eventually forming a highly structured large spheroid. Non-tumorigenic cells did not undergo coalescence. Because histological sections of melanomas forming in patients suggest that melanoma cells migrate and coalesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 108 publications
0
55
3
2
Order By: Relevance
“…Our results are different to previous 3D studies that show melanoma nests are formed by cell migration [5]. We anticipate that the difference in our outcome could be due to: (i) differences between the melanoma cell lines used; (ii) the interaction of melanoma cells with the surrounding skin cells in our 3D experiments; or, (iii) differences in the material used to construct the 3D model.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…Our results are different to previous 3D studies that show melanoma nests are formed by cell migration [5]. We anticipate that the difference in our outcome could be due to: (i) differences between the melanoma cell lines used; (ii) the interaction of melanoma cells with the surrounding skin cells in our 3D experiments; or, (iii) differences in the material used to construct the 3D model.…”
Section: Resultscontrasting
confidence: 96%
“…Recent 3D experimental work by Wessels et al . [5] suggests that melanoma nest formation in Matrigel is driven by cell migration. However, nest formation might be different in human skin, where melanoma cells are in contact with other cell types [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Tumors form in a 3D environment Therefore, in vitro studies of cancer cell behavior should be performed in a 3D model. [1][2][3] We recently reported that both tumorigenic cell lines and fresh tumor cells, when dispersed in a transparent 3D Matrigel environment, divide and undergo directed, cell-mediated cell aggregation and aggregate coalescence ("aggregation and coalescence"). [1][2][3] Non-tumorigenic cell lines and normal cell cultures derived from non-cancerous tissue, do not exhibit these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] We recently reported that both tumorigenic cell lines and fresh tumor cells, when dispersed in a transparent 3D Matrigel environment, divide and undergo directed, cell-mediated cell aggregation and aggregate coalescence ("aggregation and coalescence"). [1][2][3] Non-tumorigenic cell lines and normal cell cultures derived from non-cancerous tissue, do not exhibit these behaviors. [1][2][3] In time, large aggregates formed by tumorigenic cells assume forms consistent with the tumors formed in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation